Co-construcción de Soluciones Barriales Participativas, caso de estudio: barrio El Retorno de la parroquia Sabanilla, cantón Zamora, provincia de Zamora Chinchipe, 2022. - Gueledel Abrigo, Lidia Elizabeth (2023)
Using participatory, independent, and democratic processes, the following research work aims to assist the neighborhood "El Retorno" in developing effective solutions, geared toward meeting the needs of its citizens in accordance with local reality, with the aim of empowering citizenship and allowing active participation. Consequently, three specific objectives were established, including promoting the organization and participation of the residents of the El Retorno neighborhood, collaborating with the neighborhood in the development of collective diagnoses of the problems identified, and assisting residents with developing solutions to those problems. Several methods were used in the research, including descriptive, analytical-synthetic and deductive. Likewise, information was obtained through literature review, interviews, surveys and observation sheets, in order to know the problems affecting the neighborhood by analyzing four variables which are: infrastructure, signage, security and environment, which require intervention by competent authorities, the neighborhood directive and the residents for an effective solution and improvement of the neighborhood. The main results obtained from the present investigation are focused on three problems. Among these are two related to infrastructure, such as the absence of drinking water and the absence of a public sewerage system that affect 100% of the population, i.e., no citizen has access to these services. Thirdly, landslides occur frequently due to water seepage and affect the families living in the neighborhood because human settlements and houses are in a risk zone.